2017
DOI: 10.1242/dmm.028118
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilamodel of myeloproliferative neoplasm reveals a feed-forward loop in the JAK pathway mediated by p38 MAPK signalling

Abstract: Myeloproliferative neoplasms (MPNs) of the Philadelphia-negative class comprise polycythaemia vera, essential thrombocythaemia and primary myelofibrosis (PMF). They are associated with aberrant numbers of myeloid lineage cells in the blood, and in the case of overt PMF, with development of myelofibrosis in the bone marrow and failure to produce normal blood cells. These diseases are usually caused by gain-of-function mutations in the kinase JAK2. Here, we use Drosophila to investigate the consequences of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Various studies demonstrated Erk MAPK pathway was involved in cellular proliferation and migration ( Khodosevich, 2009 ; Wu et al, 2014 ). Although p38 MAPK pathway is normally associated with anti-proliferative and apoptotic functions ( Wagner & Nebreda, 2009 ), it was also reported that p38 was implicated in pro-survival functions, including positively regulating proliferation, differentiation and anti-apoptosis ( Halawani et al, 2004 ; Ricote et al, 2006 ; Terriente-Félix et al, 2017 ; Thornton et al, 2008 ). MAPK/Erk, Akt and p38 MAPK pathways were required for the migration of cortical neurons upon HGF stimulation ( Segarra et al, 2006 ), however, we observed GDF11 significantly suppressed the migratory capacity of C17.2 neural stem cells with the activation of Erk MAPK, PI3K/Akt and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrated Erk MAPK pathway was involved in cellular proliferation and migration ( Khodosevich, 2009 ; Wu et al, 2014 ). Although p38 MAPK pathway is normally associated with anti-proliferative and apoptotic functions ( Wagner & Nebreda, 2009 ), it was also reported that p38 was implicated in pro-survival functions, including positively regulating proliferation, differentiation and anti-apoptosis ( Halawani et al, 2004 ; Ricote et al, 2006 ; Terriente-Félix et al, 2017 ; Thornton et al, 2008 ). MAPK/Erk, Akt and p38 MAPK pathways were required for the migration of cortical neurons upon HGF stimulation ( Segarra et al, 2006 ), however, we observed GDF11 significantly suppressed the migratory capacity of C17.2 neural stem cells with the activation of Erk MAPK, PI3K/Akt and p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrated MAPK/Erk pathway was involved in cellular proliferation and migration (Khodosevich 2009;Wu et al 2014). Although p38 MAPK pathway is normally associated with anti-proliferative and apoptotic functions (Wagner & Nebreda 2009), it is also reported that p38 is implicated in prosurvival functions, including positively regulate proliferation, differentiation and antiapoptosis (Halawani et al 2004;Ricote et al 2006;Terriente-Félix et al 2017;Thornton et al 2008). MAPK/Erk, Akt and p38 MAPK pathways were required for the migration of cortical neurons upon HGF stimulation (Segarra et al 2006), however, we observed GDF11 significantly suppressed the capacity of C17.2 neural stem cells to migrate with the activation of Erk MAPK, PI3K/Akt andp38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae with a hop gain-of-function mutation always show hypertrophic lymph glands [ 68 ]. Consistently, ectopic expression of hop in the CZ, but not in the MZ, led to hyperplasia of the lymph gland, which requires Stat92E, Dome, and Upd3 [ 69 ]. In lymph glands with either the hop hypermorphic mutation or hop overexpression, an increased number of lamellocytes was also observed, even without parasitization [ 68 , 69 ].…”
Section: Regulatory Signaling During Lymph Gland Developmentmentioning
confidence: 94%
“…Consistently, ectopic expression of hop in the CZ, but not in the MZ, led to hyperplasia of the lymph gland, which requires Stat92E, Dome, and Upd3 [ 69 ]. In lymph glands with either the hop hypermorphic mutation or hop overexpression, an increased number of lamellocytes was also observed, even without parasitization [ 68 , 69 ]. Together, these results suggest that JAK-STAT signaling possesses the ability to enhance blood cell proliferation and induce lamellocyte formation in lymph glands.…”
Section: Regulatory Signaling During Lymph Gland Developmentmentioning
confidence: 94%